تأثير طريقة التدريب المدمج على التحضير البدني والمهاري لدى لاعبي كرة القدم اقل من 15سنة دراسة ميدانية لأكاديمية عين الخضراء لكرة القدم - طويل, نور الاسلام (My University, 2020)
ملخص الدراسة 1-عنوان الدراسة : تأثير طريقة التدريب المدمج على الإعداد البدني والمهاري لدى لاعبي كرة القدم اقل من15سنة. 2-أهداف الدراسة : -يهدف البحث إلى التعرف على مدى تأثير طريقة التدريب المدمج في تحسين الإعداد البدني والتعلم المهاري لدى لاعبي كرة القدم اقل من 15سنة. -تصميم برنامج تدريبي بطريقة التدريب المدمج لتحسين الجانب البدني والمهاري لدى لاعبي كرة القدم. 3-التساؤل العام: هل تؤثر طريقة التدريب المدمج على التدريب البدني والمهاري لدى لاعبي كرة القدم ؟ 4-التساؤلات الجزئية: -هل هناك فروق ذات دلالة إحصائية بين الاختبارات البدنية والمهارية القبلية والبعدية للعينة التدريبية ؟ - هل هناك فروق ذات دلالة إحصائية في الاختبارات البدنية والمهارية البعدية بين العينة الضابطة والعينة التجريبية ؟ -هل هناك فروق ذات دلالة إحصائية بين الاختبارات المهارية والبدنية القبلية والبعدية للعينة الضابطة ؟ 5-فرضيات الدراسة : أ- الفرضية العامة : - تؤثر طريقة التدريب المدمج إيجابا على التدريب البدني والمهاري لدى لاعبي كرة القدم. ب- الفرضيات الجزئية: - هناك فروق ذات دلالة إحصائية بين الاختبارات البدنية والمهارية القبلية والبعدية للعينة التدريبية - هناك فروق ذات دلالة إحصائية في الاختبارات البدنية والمهارية البعدية بين العينة الضابطة والعينة التجريبية . - لتوجد فروق ذات دلالة إحصائية بين الاختبارات المهارية والبدنية القبلية والبعيدة للعينة الضابطة 4-عينة الدراسة : 30لاعب من فريق أكاديمية وداد عين الخضراء. 5-المجال ألزماني والمكاني: تم إجراء هذه الدرسة على مستوي ولاية المسيلة بلدية عين الخضراء الملعب البلدي محمود قاسمي . بعد قبول موضوع الدراسة تم البدء في البحث من 1جانفي إلي يومنا هذا . 6-المنهج المتبع : المنهج التجريبي . 7- ادوات جمع البيانات : الاختبارات البدنية والمهارية. -الوسائل البيداغوجية . -الأساليب الإحصائية. -المراجع المختلفة . Study summary: 1- Study tillé: The effect of the combined training method on the physical and skill preparation of soccer players under 15 years old. 2- Objectives of the study: The research aims to identify the impact of the blended training method on improving physical preparation and skill learning among football players less than 15 years old. Designing a training program in the manner of blended training to improve the physical and skills aspects of football players. 3- General inquiry: Does the blended training method affect the physical and skill training of soccer players? 4- Partial questions: Are there statistically significant differences between the physical and skills tests, pre and post, for the training sample? Are there statistically significant differences in the dimensional physical and skill tests between the control sample and the experimental sample? Are there statistically significant differences between the tribal and dimensional skill and physical tests of the control sample? 5- Study hypotheses: A- General hypothesis: The blended training method positively affects the physical and skill training of soccer players. B- Partial hypotheses: - There are statistically significant differences between the physical and skills tests before and after the training sample There are statistically significant differences in the dimensional physical and skill tests between the control sample and the experimental sample. - There were no statistically significant differences between the tribal and distant skill and physical tests of the control sample 4- Study sample: 30 players from the Widad Ain Al-Khadra academy. 5- Temporal and spatial domain: This study was conducted at. the level of M'sila wilaya, Ain al-Khadra municipality, Mahmoud Qasimi municipal stadium. After acceptance of the study topic, research was started from January 1 to the present day. 6- The Approach: The Experimental Approach: Physical and skill tests. Teaching methods. Statistical methods. Various references. 7- Key words in the study: Blended Training. Training methods. Physical preparation. Skill learning. Football.
Keywords: التدريب المدمج; طرق التدريب; الإعداد البدني; التعلم المهاري; كرة القدم